Efektifitas Pengelolaan Dan Pengumpulan Zakat Profesi (Pns) Di Unit Pengumpul Zakat (Upz) Baznas Kecamatan Cluring - Yeni Rokhilawati (Jurnal Istiqro, 2018)
This study is to analyze the effectiveness of Zakat, Infaq, and Alms (ZIS) fundraising after the BAZNAS Banyuwangi decree No: KP.BAZNAS / BWI / A.01.SK / 30/2016 concerning the management of Zakat, Infaq, Alms at the Subdistrict level in collecting zakat profession (PNS) in the Zakat Collection Unit (UPZ) BAZNAS Cluring District, which aims to find out the supporting and inhibiting factors in the collection of professional zakat funds in Zakat Collectors (UPZ) BAZNAS Cluring District and provide solutions to overcome the obstacles to the collection of professional zakat funds in the Zakat Collection (UPZ) BAZNAS in Cluring District. The results of the study show that the PNS professional zakat fund collection obtained from 9 local government agencies in Cluring District from the establishment of the Zakat Collection Unit (UPZ) of BAZNAS in Cluring District in December 2015 to date is quite effective because every month the collection of professional zakat funds always shows an increase in value.